Querido Pedrin - Ada, Alma Flor.; Tryon, Leslie (New York : Atheneum ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1994)
Presents letters between such fairy tale characters as Goldilocks, Baby Bear, Peter Rabbit, and the Three Pigs.
Keywords: Characters and characteristics in literature -- Juvenile fiction; Spanish language materials -- Juvenile fiction; Letters -- Juvenile fiction